PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN SISTEM LOGBOOK NELAYAN (CELEBESREEFFISH.COM) UNTUK KEBERLANJUTAN USAHA PERIKANAN NELAYAN - Mauli Kasmi; Syamsul Marlin Amir; Andryanto A; Arif Fuddin Usman; Andi Ridwan Makkulawu; Akmal Abdullah; Muhammad Irhan Latif (LPPM Universitas Bina Bangsa, 2023)
The purpose of this community service is to improve the empowerment of fishing communities in Pangkajene and Kepulauan Regency through the implementation of a fisherman logbook system (celebesreeffish.com). During the implementation of this PIPK Program, the results obtained include significant adoption by fishing communities of the fisherman logbook system, increased efficiency in recording fisheries catches, increased understanding of ornamental fish species, and increased collaboration between fishermen and local governments in maintaining the sustainability of marine resources. This activity is a form of supporting the vision and mission of the Pangkajene and Islands Regency Government in realizing a prosperous, superior, competitive, and religious civil society, based on sustainable local resources, especially in marine/fisheries-based community economic development, which is one of the Government's priority programs. This program strengthens the role of fishermen in conserving marine resources and improving their quality of life, in line with sustainable development goals